HUBUNGAN STATUS GIZI DENGAN WAKTU PENYEMBUHAN LUKA DEKUBITUS PADA PASIEN IMOBILITAS DI RUMAH SAKIT UMUM DAERAH DR. PIRNGADI - Loisa Tobing; Mhd. Taufik Daniel Hasibuan (Universitas Murni Teguh, 2026)
Abstract Pressure ulcers are serious complications in immobile patients that increase infection risks and healthcare costs. While nutritional status plays a vital role in tissue regeneration, malnutrition often hinders the recovery process. The objective of this study is to determine the relationship between nutritional status and the healing time of pressure ulcers among immobile patients at RSUD Dr. Pirngadi. This quantitative study used a cross-sectional approach with 33 pressure ulcer patients (total sampling). Nutritional status was measured using Body Mass Index (BMI), while healing time was calculated in days. Data were analyzed using the Spearman correlation test. There was a significant correlation between nutritional status and the healing time of pressure ulcers (r=−0,581; p<0,001). The negative correlation indicates that better nutritional status is significantly associated with a shorter recovery time. Good nutritional status significantly accelerates the healing of pressure ulcers in immobile patients. Comprehensive nutritional intervention and monitoring should be an integral part of patient care management to prevent complications and expedite recovery.